Bài 4
Ta xét vế trái
$3x^2 + 5y^2 +4xy +8x - 2y + 9 = x^2 + 4xy + 4y^2 + 2x^2 + 8x + 8 + y^2 - 2y + 1$
$= (x+2y)^2 + 2(x^2 + 4x + 4) + (y-1)^2$
$= (x+2y)^2 + 2(x+2)^2 + (y-1)^2 \geq 0$ với mọi $x, y$
Bài 5
Để ptrinh
$(m-3)x^2 + (2m+1)x + m + 2 \geq 0$
vô nghiệm thì
$(m-3)x^2 + (2m+1)x + m + 2 < 0$ với mọi $x$.
Do đó $m - 3<0$ và $\Delta < 0$.
Vậy $m < 3$ và
$(2m+1)^2 - 4(m-3)(m+2) < 0$
$<-> 4m^2 + 4m + 1 - 4(m^2 -m - 6) < 0$
$<-> 4m^2 + 4m + 1 -4m^2 + 4m + 24 < 0$
$<-> 8m+ 25 < 0$
$<-> m < -\dfrac{25}{8}$
Vậy $m < -\dfrac{25}{8}$.